2014
DOI: 10.1093/hmg/ddu608
|View full text |Cite
|
Sign up to set email alerts
|

HSP47 and FKBP65 cooperate in the synthesis of type I procollagen

Abstract: Osteogenesis imperfecta (OI) is a genetic disorder that results in low bone mineral density and brittle bones. Most cases result from dominant mutations in the type I procollagen genes, but mutations in a growing number of genes have been identified that produce autosomal recessive forms of the disease. Among these include mutations in the genes SERPINH1 and FKBP10, which encode the type I procollagen chaperones HSP47 and FKBP65, respectively, and predominantly produce a moderately severe form of OI. Little is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 33 publications
3
52
2
1
Order By: Relevance
“…In the present study, we did not detect causative mutations in the SERPINH1 gene and there are few cases of reported mutations in SERPINH1 causing OI (Christiansen et al, 2010;Duran et al, 2015). Therefore, pathogenic changes in the SERPINH1 gene are thought to be very rare in OI patients.…”
Section: Discussioncontrasting
confidence: 63%
“…In the present study, we did not detect causative mutations in the SERPINH1 gene and there are few cases of reported mutations in SERPINH1 causing OI (Christiansen et al, 2010;Duran et al, 2015). Therefore, pathogenic changes in the SERPINH1 gene are thought to be very rare in OI patients.…”
Section: Discussioncontrasting
confidence: 63%
“…Mechanistically, Hsp47 regulates triple-helix stability via direct binding to specific arginine residues that lie at the interface between Hsp47 and collagen [6668]. Loss of function mutations in HSP47 causes recessive OI due to aggregation and delayed secretion of procollagen molecules [69,70]. While Hsp47 is not directly involved in the post-translational modification of collagen, loss of function mutations of HSP47 (p.L326P) in a dog OI model caused overmodification of type I collagen and increased cross-linking without affecting 3Hyp (Pro986) [71].…”
Section: Genetic Causes and Mechanisms Of Osteogenesis Imperfectamentioning
confidence: 99%
“…This indicates that structural defects of collagen may contribute to abnormalities in post-translational modification. Given that FKBP65 and HSP47 co-eluted in a velocity sedimentation experiment [47] and were also shown to interact by proximity ligation assay, it is possible that HSP47 associates with the FKBP65/LH2 complex, albeit in a weak or transient fashion [69]. …”
Section: Genetic Causes and Mechanisms Of Osteogenesis Imperfectamentioning
confidence: 99%
“…After all the modifications are complete and the triple helix is formed, the molecules of procollagen are transported along microtubules, organized in the Golgi apparatus, and eventually secreted into the extracellular space [56]. In a homozygous patient with HSP47 missense mutation, it was demonstrated that HSP47, potentially acting in cooperation with immunophilin FKBP65, encoded by FKBP10, is important for proper trafficking of type I procollagen to the Golgi [57]. Mutations in FKBP10 also cause moderately severe osteogenesis imperfecta [58,59] with decreased collagen cross-linking, resulting in sparsity and disorder of collagen fibril deposition [60].…”
Section: Potential Signaling Induced During Collagen Synthesis By Ostmentioning
confidence: 99%